Intranet effectiveness and organizational commitment. - Weber, Paull C. (Curtin University, 2002)
The Intranet Pencil and Paper Checklist (Murgolo-Poore et al., 2002) is a new measure developed to gauge the perceptions of organization members as to the effectiveness of the firms Intranet, from an Internal Marketing and Human Resource perspective. Three dimensions of the construct "Intranet Effectiveness " have been distilled from initial scale development research and testing, they are Operations, Facilitation and Culture.The instrument is now applied to a financial services organization with approximately 3000 staff to test its robustness across all layers of a hierarchy. It performed well, particularly in plumbing the perceptions of management towards their Intranet.Several theoretical perspectives were investigated to understand how OC and Intranet effectiveness may be associated, including Transaction Cost Theory, Communication Theory and Social Identity Theory. With this theoretical underpinning the instrument was administered to discern if an effective Intranet, through its power to communicate and involve multiple stakeholders had any correlation with Organizational Commitment.Intranet effectiveness was found to have a significant correlation, which varied in its effect across user groups. It was suggested as a focus for future research that peripheral groups might have benefited from the Intranet in a way that increased OC amongst those cohorts disproportionately. Should such a theory be borne out by empirical investigation, it has potential application for strategic decision making in Intranet design and management.